2022
DOI: 10.1051/0004-6361/202142337
|View full text |Cite
|
Sign up to set email alerts
|

A candidate short-period sub-Earth orbiting Proxima Centauri

Abstract: Context. Proxima Centauri is the closest star to the Sun. This small, low-mass, mid M dwarf is known to host an Earth-mass exoplanet with an orbital period of 11.2 days within the habitable zone, as well as a long-period planet candidate with an orbital period of close to 5 yr. Aims. We report on the analysis of a large set of observations taken with the ESPRESSO spectrograph at the VLT aimed at a thorough evaluation of the presence of a third low-mass planetary companion, which started emerging during a previ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 80 publications
1
51
0
Order By: Relevance
“…On the same subject, more recent works (e.g. Hara et al 2019 andFaria et al 2022), discuss the issue that orbital eccentricities fitted using only RVs could be spurious, as a consequence of an inappropriate modelling or not optimal data quality relative to the low semi-amplitude of the signal. Hara et al (2019) showed how one can get a wrong inference of the eccentricity without including an uncorrelated jitter term in the model and, more importantly, an incorrect result without a proper modelling of correlated signals, such as stellar activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the same subject, more recent works (e.g. Hara et al 2019 andFaria et al 2022), discuss the issue that orbital eccentricities fitted using only RVs could be spurious, as a consequence of an inappropriate modelling or not optimal data quality relative to the low semi-amplitude of the signal. Hara et al (2019) showed how one can get a wrong inference of the eccentricity without including an uncorrelated jitter term in the model and, more importantly, an incorrect result without a proper modelling of correlated signals, such as stellar activity.…”
Section: Discussionmentioning
confidence: 99%
“…Hara et al (2019) showed how one can get a wrong inference of the eccentricity without including an uncorrelated jitter term in the model and, more importantly, an incorrect result without a proper modelling of correlated signals, such as stellar activity. Faria et al (2022) showed how the value of the eccentricity of Proxima d depends on the method used to extract the RVs from ESPRESSO spectra, with a better constraint obtained using a technique based on template matching. In our analysis, we included uncorrelated jitter terms, we showed that the result is independent from the model used to fit the correlated stellar activity signal, and we tested our finding against different RV extraction methods applied to HARPS spectra.…”
Section: Discussionmentioning
confidence: 99%
“…The masses of the lowest-mass planets (which are also from the NASA Exoplanet Archive) in the systems are indicated by the color bar at the right side of the upper panel. A low-mass planet recently discovered around Proxima Centauri (Faria et al 2022) was included in the plots.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Planets have been detected around very low mass (VLM) stars, defined as stars with masses 0.3 M , yet still above the hydrogen-burning limit at ∼ 0.08 M , below which the brown dwarf regime begins (Liebert & Probst 1987). Particularly fasci-nating are the cases of TRAPPIST-1, a ∼ 0.085 M star in the Solar neighborhood with a system of 7 rocky planets (Gillon et al 2017), and Proxima Centauri, the closest star to the Sun with a mass of ∼ 0.12 M , which hosts a terrestrial planet, a super-Earth candidate, and a newly discovered sub-Earth candidate (Anglada-Escudé et al 2016;Damasso et al 2020, Faria et al 2022. In general, data from the Kepler spacecraft show that the occurrence rate of small planets (with a radius of 1.0 − 2.8 R ⊕ ) is 3.5 times higher for M dwarfs than FGK stars (Mulders et al 2015).…”
Section: Introductionmentioning
confidence: 99%